Reproductive tract and pouch anatomical variability across the reproductive phases in female common opossum (Didelphis marsupialis Linnaeus, 1758) - Andrés Sepúlveda-Vásquez; Claudia P. Ceballos; Lynda J. Tamayo-Arango (PLoS ONE, 2025)
Colombia’s diverse ecosystems are home to various marsupial species known for its distinctive reproductive traits. Limited research has explored the reproductive anatomy of Didelphis marsupialis, particularly regarding variations associated with reproductive phase. This study aimed to characterize the reproductive anatomy of female D. marsupialis and assess its relationship with reproductive phases. We analyzed 57 female opossum cadavers using dissection, histology, and biometry. Specimens were classified by life stage based on dental chronology and by reproductive phase—interestrus, proliferative, and diestrus—based on ovarian features. Among the specimens, 79% lacked pouch young, while 21% carried young with an average of 3 individuals (range = 1–7). Uterine dimensions varied with the reproductive phase, with the pregnant female displaying the largest measurements. Five teats were commonly observed in adults (range = 0–10), while subadults exhibited the highest mean teat count (eleven), suggesting an adaptability to the reproductive demands. We identify six distinct anatomical variations in the vaginal complex, including the inconstant presence of a vaginal sinus septum and diverse cul-de-sac configurations. These variations allow us to reconstruct the temporary formation and subsequent regression of the birth canal, characterized by an invagination of the vaginal sinus and epithelial lining during pregnancy, followed by a postpartum involution. Additionally, we propose to use the term “urogenital canal” over “urogenital sinus” as it is more accurate anatomically. Future research should address the timing of the birth canal formation and regression and its relationship with the mammary gland development in living individuals.